Análise do gerenciamento de pacientes crônicos atendidos por operadora de saúde suplementar - Sousa, Gilmar Oliveira de [UNIFESP] (2017)
This study was carried out in a health care program of a supplementary health care provider in the southern region of Bahia, comprising a multidisciplinary team. It is a retrospective, documentary research with a quantitative approach. Data were collected in 2016 for the years 2012-2015. With the general objective of analyzing the home care program managed by a health care provider in Itabuna-Bahia and as specific objectives: to characterize the sociodemographic and clinical profile of the beneficiaries served by the program; To know the costs / year by period of the program, aiming at a better operationalization of the resources invested in the health management of the assisted population. Considering to obtain the results with effectiveness and efficiency, obtaining strategies of interventions, with actuation and valorization of the autonomy of Nursing in this process. In this study, ethical aspects were observed, preceded by the approval of the Unifesp Ethics Committee resolution number 1,592,711 / 2016 and CEP / UESC protocol number 822.937 / 2015. Results: In this period, 300 patients with chronic diseases, including diabetes, Alzheimer's disease, hypertension, chronic obstructive pulmonary disease (COPD) and / or patients underwent complex procedures (neurological and traumatologic surgeries, among others). The majority of beneficiaries attended by the program were female (59.67%); With 70 years or more (59%). As for incomplete first grade schooling was (33%); High school (22%); Higher education level (4.33%); And the family wage range between 2 to 3 minimum wages (30%), 3 to 5 minimum wages (18.33%) and retirees (49%). In relation to the costs of the health care provider with its users before and after insertion in the health care program (PAS) in the health management modality, a significant reduction of these costs is noticed. Before the PAS annual value of R $ 747,036.65 and after the PAS after the first year was R $ 281,276.42, a percentage reduction of the cost of 62.35%. Conclusion: The importance and efficacy of a chronic patient management program was observed not only for the financial health of a supplementary health care provider, but also for the health management of a population that still lacks technical and educational resources. Can make the difference in their walk in search of a quality of life and a longevity with security and using only basic resources, but primordial for their health. This study, although limited in scope, shows that a health management program in the region, in the current context of human aging, is of fundamental importance, especially for the bedridden patient. Without this, the increase in the cost of any health care provider is notorious, since the patient is adrift in the knowledge of health care, reducing the quality of life deficit, further increasing the cost of worsening health.